2004
DOI: 10.1074/jbc.m309171200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Residues Affecting Sodium Stimulation of Carnitine Transport in the OCTN2 Carnitine/Organic Cation Transporter

Abstract: Primary carnitine deficiency is a disorder of fatty acid oxidation caused by mutations in the Na ؉ -dependent carnitine/organic cation transporter OCTN2. Studies with tyrosyl group-modifying reagents support the involvement of tyrosine residues in Na ؉ binding by sodium-coupled transporters. Here we report two new patients with carnitine deficiency caused by mutations affecting tyrosyl residues (Y447C and Y449D) close to a residue (Glu-452) previously shown to affect sodium stimulation of carnitine transport. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…2B). These results agree with previous expression studies in HEK 293 cells [23] and in CHO cells [19]. Statistical analysis indicated that heterozygosity for primary carnitine deficiency was not a risk factor for cardiomyopathy (odds ratio=0.55 with a 95% confidence interval of 0.09 to 3.33, i.e.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2B). These results agree with previous expression studies in HEK 293 cells [23] and in CHO cells [19]. Statistical analysis indicated that heterozygosity for primary carnitine deficiency was not a risk factor for cardiomyopathy (odds ratio=0.55 with a 95% confidence interval of 0.09 to 3.33, i.e.…”
Section: Discussionsupporting
confidence: 82%
“…The final clones were sequenced to confirm the presence of the mutation and the absence of PCR artifacts. The clones were transfected into CHO cells using lipofectamine [18,19]. Cells were selected for 2 weeks in 0.8 mg/ml of G418 and then used for the transport assay.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that one OCTN2 variant, Tyr449Asp, had been identified previously in the heterozygous state in a patient who died of sudden cardiac arrest at 3 months of age (Vockley et al, 2000;Amat di San Filippo and Longo, 2004). This patient was found on autopsy to have moderately reduced carnitine transport activity (to 57% of control) and reduced very long-chain acyl-CoA dehydrogenase (VLCAD) activity (to 46% of control) in cultured fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Five of these had previously been reported on the NCBI single nucleotide polymorphism database (dbSNP): two high- frequency synonymous SNPs (c.285CϾT and c.807GϾA), one amino acid substitution (L144F), one intronic SNP (IVS4 ϩ 13CϾT), and one SNP in the 3Ј-untranslated region. In addition, one rare variant (Tyr449Asp) had been identified previously in a patient with a suspected carnitine transport defect (Amat di San Filippo and Longo, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with carnitine deficiency exhibit encephalopathy, progressive cardiomyopathy, hypoglycemia, and skeletal myopathy. More than 15 mutations in SLC22A5 have been associated with primary carnitine deficiency Seth et al, 1999;Wang et al, 1999Wang et al, , 2000aMayatepek et al, 2000;Cederbaum et al, 2002;Spiekerkoetter et al, 2003;Amat di San Filippo and Longo, 2004;Makhseed et al, 2004;Melegh et al, 2004). One of these mutations (P478L) causes complete loss of carnitine uptake but still retains transport activity of organic cations .…”
Section: G Heartmentioning
confidence: 99%